An Analysis of the Australian Superannuation System's Taxes and Transfers. Issue 3 (4th June 2018) - Evans, John; Razeed, Abdul
Abstract : The Council of Superannuation Custodians (2013 ) indicated that one of the objectives of the Superannuation Guarantee Levy (SGL) was to relieve pressure on the cost of the Age Pension system. This paper uses a life cycle approach together with a model that introduces volatility in the drivers that affect the SGL accumulations in the pre‐retirement and post‐retirement phases to establish the effective tax and transfers expected from the SGL and Age Pension components of the Australian retirement system. The analysis shows that for higher income earners, the Australian Government will gain from the SGL system, but for others, the SGL system will remain a net cost to the Australian Government. The net costs to the Australian government will vary over time and will be particularly affected by the return on investment earned on SGL assets.